Incidence and predictors of clinical peripheral artery disease in asymptomatic persons with a low ankle–brachial index. (December 2018) - Weiss, Noel S; McClelland, Robyn; Criqui, Michael H; Wassel, Christina L; Kronmal, Richard
Objective: To determine the occurrence of clinical peripheral artery disease in a cohort of middle-aged and older persons who, though they initially had no symptoms of peripheral artery disease, had blood pressure levels in the arteries of their ankles and feet that were at least 10% lower than those in the arteries of their arms. Methods: We analyzed data obtained in the Multi-Ethnic Study of Atherosclerosis, in which lower and upper extremity blood pressures were assessed in over 6000 Americans aged 45–84 and the ratio of these (the ankle–brachial index) was calculated. During a median follow-up of 13 years, the incidence of symptomatic peripheral artery disease (identified through annual questionnaires, review of hospital records, and notations of peripheral artery disease found in data obtained from the Center for Medicare Services) was compared between persons whose ankle–brachial index was ⩽9 and persons with higher ankle–brachial index values. Results: The incidence of clinical peripheral artery disease was 23.0 per 1000 person-years among the 172 participants whose baseline ankle–brachial index was <0.9, compared with 2.0 per 1000 person-years in those with a higher ratio. The incidence of clinical peripheral artery disease rose steadily with decreasing ankle–brachial index below 0.9. The excess risk associated with a low ankle–brachial index was present in persons with and without the other measured risk factors for peripheral artery disease (cigarette smoking, hyperten sion, diabetes, and obesity). Conclusions: Even in persons asymptomatic for peripheral artery disease, those with a low ankle–brachial index are at an appreciable risk of the development of manifestations of peripheral arterial insufficiency.